Grammar-Translation and Direct Methods in Teaching English in the Educational Institution with Specific Conditions of Study - Shenderuk, O.B.; Tamarkina, O.L; Pernarivska, Tetiana Petrivna (The Journal of Social Sciences Research, 2018)
Needless to say, the role of foreign languages has a vital importance nowadays (Fazal et al., 2016). It holds a dominant position in all spheres of human activity. To update your knowledge and learn about new intentions you should learn English well (Reddy, 2012; Shatrova, 2014). The increasing role of English made the issue of various methods, techniques and approaches very actual.

Потрібно зазначити, що роль іноземних мов на сьогодні має життєво важливе значення (Fazal et al., 2016). Знання мов займає домінуюче положення у всіх сферах людської діяльності. Щоб оновити свої знання та дізнатися про нові наміри, ви повинні добре вивчити англійську мову (Reddy, 2012; Shatrova, 2014). Зростаюча роль англійської мови актуалізувала питання різних методів, прийомів та підходів які застосовуються під час її вивчення.
Keywords: English teaching methods; approaches; advantages and disadvantages; cadets and students; peculiarities of study; методи навчання англійської мови; підходи; переваги і недоліки; курсанти та студенти; особливості навчання